Histological changes and impairment of liver mitochondrial bioenergetics after long-term treatment with alpha-naphthyl-isothiocyanate (ANIT) - Palmeira, CM (2010)
This study was designed to evaluate the effects of long-term treatment with alpha-naphthyl-isothiocyanate (ANIT) on liver histology and at the mitochondrial bioenergetic level. Since, ANIT has been used as a cholestatic agent and it has been pointed out that an impairment of mitochondrial function is a cause of hepatocyte dysfunction leading to cholestatic liver injury, serum markers of liver injury were measured and liver sections were analyzed in ANIT-treated rats (i.p. 80 mg/kg/week x 16 weeks). Mitochondrial parameters such as transmembrane potential, respiration, calcium capacity, alterations in permeability transition susceptibility and ATPase activity were monitored. Histologically, the most important features were the marked ductular proliferation, proliferation of mast cells and the presence of iron deposits in ANIT-treated liver. Mitochondria isolated from ANIT-treated rats showed no alterations in state 4 respiration, respiratory control ratio and ADP/O ratio, while state 3 respiration was significantly decreased. No changes were observed on transmembrane potential, but the repolarization rate was decreased in treated rats. Consistently with these data, there was a significant decrease in the ATPase activity of treated mitochondria. Associated with these parameters, mitochondria from treated animals exhibited increased susceptibility to mitochondrial permeability transition pore opening (lower calcium capacity). Since, human cholestatic liver disease progress slowly overtime, these data provide further insight into the role of mitochondrial dysfunction in the process.